2021
DOI: 10.1002/cssc.202102136
|View full text |Cite
|
Sign up to set email alerts
|

New‐Generation Carbon‐Capture Ionic Liquids Regulated by Metal‐Ion Coordination

Abstract: Development of efficient carbon capture-and-release technologies with minimal energy input is a long-term challenge in mitigating CO 2 emissions, especially via CO 2 chemisorption driven by engineered chemical bond construction. Herein, taking advantage of the structural diversity of ionic liquids (ILs) in tuning their physical and chemical properties, precise reaction energy regulation of CO 2 chemisorption was demonstrated deploying metal-ion-amino-based ionic liquids (MAILs) as absorbents. The coordination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The absorption capacity (mol/kg) decreased in the order of [C 5 ] < [C 6 ] < [C 7 ], and [EHA][C 7 ] showed the highest absorption capacity (∼3.0 mol/kg at 29 bar and room temperature). Taking the advantage of metal ion coordination, Suo et al (2022) synthesized metal-ion-amino-based IL using metal salts {[M(OctNH 2 ) 4 ][NTf 2 ] 2 , M = Co, Cu, Ni, Zn, and Mg}. The CO 2 absorption capacity (mol/kg) followed the order of [Li(OctNH 2 ) 4 ][NTf 2 ] 2 > [Mg (DecNH 2 ) 4 ][NTf 2 ] 2 ≈ [Mg(OctNH 2 ) 4 ][NTf 2 ] 2 > [Ni(OctNH 2 ) 4 ][NTf 2 ] 2 > [Ni(DecNH 2 ) 4 ][NTf 2 ] 2 > [Co(OctNH 2 ) 4 ][NTf 2 ] 2 > [Zn(OctNH 2 ) 4 ][NTf 2 ] 2 > [CuMg(DecNH 2 ) 4 ][NTf 2 ] 2 > [Cu(OctNH 2 ) 4 ][NTf 2 ] 2 > [CuZnNiMg(DecNH 2 ) 4 ][NTf 2 ] 2 > [CuZn(DecNH 2 ) 4 ][NTf 2 ] 2 .…”
Section: Literature Survey Data Collection Properties Perdition and I...mentioning
confidence: 99%
“…The absorption capacity (mol/kg) decreased in the order of [C 5 ] < [C 6 ] < [C 7 ], and [EHA][C 7 ] showed the highest absorption capacity (∼3.0 mol/kg at 29 bar and room temperature). Taking the advantage of metal ion coordination, Suo et al (2022) synthesized metal-ion-amino-based IL using metal salts {[M(OctNH 2 ) 4 ][NTf 2 ] 2 , M = Co, Cu, Ni, Zn, and Mg}. The CO 2 absorption capacity (mol/kg) followed the order of [Li(OctNH 2 ) 4 ][NTf 2 ] 2 > [Mg (DecNH 2 ) 4 ][NTf 2 ] 2 ≈ [Mg(OctNH 2 ) 4 ][NTf 2 ] 2 > [Ni(OctNH 2 ) 4 ][NTf 2 ] 2 > [Ni(DecNH 2 ) 4 ][NTf 2 ] 2 > [Co(OctNH 2 ) 4 ][NTf 2 ] 2 > [Zn(OctNH 2 ) 4 ][NTf 2 ] 2 > [CuMg(DecNH 2 ) 4 ][NTf 2 ] 2 > [Cu(OctNH 2 ) 4 ][NTf 2 ] 2 > [CuZnNiMg(DecNH 2 ) 4 ][NTf 2 ] 2 > [CuZn(DecNH 2 ) 4 ][NTf 2 ] 2 .…”
Section: Literature Survey Data Collection Properties Perdition and I...mentioning
confidence: 99%
“…[26,27] Recently, bottomup approaches involving metal-ion coordinated amines as reactive CO 2 capture agents are demonstrated to lower the energy requirement and increase sorbent stability for regeneration. [28] With the increasing availability of renewable energy sources, alternative regeneration approaches that do not rely on thermal energy from fossil-fuel burning is gaining interest. There have been few reports on the microwave-based regeneration of conventional aqueous amines [29,30] and solid sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Regeneration of sorbents has traditionally relied on temperature‐swing operations and the availability of thermal energy to desorb the CO 2 and recycle the sorbent [26,27] . Recently, bottom‐up approaches involving metal‐ion coordinated amines as reactive CO 2 capture agents are demonstrated to lower the energy requirement and increase sorbent stability for regeneration [28] . With the increasing availability of renewable energy sources, alternative regeneration approaches that do not rely on thermal energy from fossil‐fuel burning is gaining interest.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that CO 2 capacity of polyamine-based ILs increased when [Li(TTEG)][Tf 2 N] or [Li(TEG)][Tf 2 N] was added, and CO 2 capacity of [Li(TEPA)][Tf 2 N]/[Li(TEG)][Tf 2 N] (weight ratio is 1:2) decreased from 2.05 to 0.83 mol per CO 2 mol IL at 80 °C when CO 2 concentration was reduced from 100 vol.% to 380 ppm. Recently, Yang, Xing, and Dai et al [ 37 ] reported the tuning of stability constants of metal-amine complexes for efficient CO 2 desorption.…”
Section: Functionalized Ils For Co 2 Capturementioning
confidence: 99%